DOSIMETRIC PAIRING OF PHOTON BEAMS OF 6 MEV OF ENERGY FROM TWO LINEAR ACCELERATORS OF THE SAME COLLIMATION SYSTEM - PACHECO, JONATHAN W. (2024)
IN RADIOTHERAPY CENTERS, WHERE THERE ARE MORE THAN TWO LINEAR ACCELERATORS (LINACS) OF THE SAME MANUFACTURER AND MODEL, IT IS IMPORTANT TO CONSIDER A DOSIMETRIC PAIRING. FOR THIS REASON, THE INITIATIVE TO COMPARE THE DOSIMETRIC FACTORS OF TWO MODELS OF LINACS SYNERGY (ELEKTA) WITH PHOTONS OF 6 MEV OF ENERGY WAS PRESENTED. TOTAL DISPERSION FACTORS, DOSE VARIATION IN THE CENTRAL AXIS, DOSE PROFILE, WEDGE TRANSMISSION FACTORS, AND DOSE RATE WERE CONSIDERED. ABSOLUTE AND RELATIVE MEASUREMENTS WERE MADE WITH 5 IONIZATION CHAMBERS, FLAT DOSE DISTRIBUTIONS WERE OBTAINED WITH AN ARRANGEMENT OF 729 IONIZATION CHAMBERS, AND THE Γ INDEX WAS EVALUATED BY MEPHYSTO SOFTWARE. THE RESULTS OBTAINED WERE DOSE DIFFERENCE VALUES OF LESS THAN 1 %, REPRODUCED DOSE DISTRIBUTIONS WITH A VALUE GREATER THAN 95 % OF THE VOXELS ANALYZED FOR DISTANCE TO AGREEMENT (DTA) OF 2 MM AND ∆ DOSE OF 2 %, BOTH FOR PDD AND FOR EVALUATED PROFILES. THESE RESULTS WERE VALIDATED WITH DATA OBTAINED WITH MONTE CARLO SIMULATION (XVMC). IT WAS CONCLUDED THAT WITH THE METHODOLOGY DEVELOPED IT WAS POSSIBLE TO OBTAIN AN ADEQUATE PAIRING OF BEAMS GENERATED BY TWO DIFFERENT LINACS. © 2024, UNIVERSIDAD NACIONAL DE COLOMBIA. ALL RIGHTS RESERVED.